Evidências preliminares da eficácia do gel contendo própolis na prevenção e no tratamento da mucosite e da candidose bucais em pacientes submetidos a radioterapia em região de cabeça e pescoço - Vladimir Reimar Augusto de Souza Noronha (2011)
During radiotherapy and chemotherapy, some side effects can be observed, leading to a considerable loss of life quality or even desertion of treatment due to the patients death. Of the effects mentioned above, the most common ones found in the oral cavity are mucositis and candidiasis. Several drugs have already been suggested as a treatment for mucositis, but none of them has shown effective pharmacological characteristics when combined with an ideal residence in the oral cavity. Propolis is a natural product that has been used by people since ancient times and it has analgesic, anti-inflammatory, antimicrobial and wound healing properties. These characteristics that have already been proved in in vitro studies, when associated with the lack of side effects originated from a mucus-bonding gel generate a great prospect for the prevention and treatment of candidiasis and superimposed musosite observed during and after radiotherapy. In the period from September/10 until March/11 33 patients were selected, of which 27 (81.8%) were males and 6 (18.2%) were females. Their mean age was about 57.36 years (±11,20). Regarding skin color, 19 (57.6%) were caucasian. The majority of patients consisted of former smokers (23 patients - 69.7%). Concerning the histological prospect, the squamous cell carcinoma was more prevalent, reaching 31 (93.9%) patients. We collected saliva from 23 patients before using propolis and of these 8 (88.9%) had C. albicans, 1 (4.7%) had C. kefyr and 9 (39.1%) presented no yeast involvement. After the gel application, the Candida sp. population diversified, which gave us a new prospect, having 6 (46.2%) patients with C. albicans, 3 (23.1%) with C. kefyr and 2 (15.4%) showed no yeasts at all. For C. tropicallis, C. parapsilosis, C. krusei, only 1 (7.7%) we found only one patient per species. The resistance to antifungal agents was more evident for fluconazole and miconazole, either prior to the gel application or after it. The 6 strains of C. albicans previously found before the gel application, were resistant to fluconazole. After the gel application, from those 6 strains of C. albicans, 3 (50%) are now resistant to fluconazole and 5 (83.3%) are resistant to miconazole. The gel containing propolis was well accepted by patients and its effectiveness can be proven by the gel containing propolis evaluation of 13 (39.4%) patients with complete data using a segmentation analysis. The result of the Fisher's exact test showed an association between the presence of mucositis during 4 weeks of propolis application and clusters (p = 0.026). In cluster 2, which consisted of patients using the propolis gel in a preventive way, no patient developed mucositis in a 4 weeks follow-up.